Guidelines for the reopening of indoor sports and associations, as well as sports and leisure facilities (phases 2 and 3) (2020)
On 8 June, DGI, DIF and Company Sports announced guidelines for sports activities spanning indoor and outdoor sports, swimming, fitness centres and gyms, summer schools and camps. The framework is based on the Ministry of Culture's "Guidelines for the reopening of sports and association life outdoors and indoors".